Interaction of Wu Zhaoqian, Gu Zhenguan and Nalan Xingde - Liew, Fong Wai (2017)
Among the studies on the interaction of Manchu and Chinese scholars in the Early Qing Dynasty, the most popular story must be of Gu Zhenguan, who was able to move the Prime Minister’s son, Nalan Xingde, with his Ci called Jinlv Qu, and successfully rescued Wu Zhaoqian who was exiled for 23 years to Ning Gu Ta, due to his involvement in an Examination Scandal. Many researchers have studied the relationship between these three scholars through the Jinlv Qu, but this Ci cannot portray the full extent of their interaction. This thesis aims to conduct a comprehensive study of their friendship by examining their literary output and history of their interaction, and organize it into a chronological table in order to examine their relationship in stages, including: (1) How they maintained their friendship via their literary output even though they rarely met; (2) How they overcame the differences between them and forged a lasting friendship based on commonalities; (3) Gu Zhenguan’s and Nalan Xingde’s vow of eternal friendship through Ci and how it formed the basis of their relationship and the resulting occurrence of a few important incidents, mostly related to Ci; (4) Gu Zhenguan’s and Nalan Xingde’s similar advocacy in writing Ci, and how this was influenced by their interaction as well; and (5) The examination of their advocacy of the revival of Qing Ci to investigate their relationship. This thesis aims to investigate the interaction between Wu Zhaoqian, Gu Zhenguan and Nalan Xingde to get a glimpse of the interaction between the literati in the early Qing dynasty, and also the link between their relationship and the Qing Ci Revival during the period.